c=6+5x

Simple and best practice solution for c=6+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for c=6+5x equation:


Simplifying
c = 6 + 5x

Solving
c = 6 + 5x

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Simplifying
c = 6 + 5x

See similar equations:

| 7x-3=24x+5 | | 7x-3=24x | | 3x+4+4y=16 | | 16=.25b | | b+2.25=5 | | 16=.25 | | 15w*1.25= | | 2(8+6x)+2=4(4+3x)+2x | | 4a^3+12a^2-9a-27=0 | | 45+40a= | | 291.52=8(0.04m+27.70+0.20(27.70)) | | 8h+9=60 | | 21=(8-c)3 | | -70=-2(x+5)+7(4-6x) | | 291.52=8(0.04m+27.70+0.20(27.20)) | | (a+b)+(a-b)-2a=72-72 | | t*5-5=13 | | 4-8(2+5v)+7= | | 21=(8-3) | | 6x+11=-127 | | 15w^2+15w^3= | | 10(x-50)=-80 | | b-17=-3 | | 2x=3y-23 | | U+15=18 | | 3(11m-13)=-7m+57+32m | | 6=2+x(3) | | (-5.62x-0.8)+(1.12+1.4)=-4.2x+0.32 | | Y=-16t^2+85t | | (-5.62x-0.8)+(1.12+1.4)= | | y=-7.78x+85 | | 9-2x+5=3x+4 |

Equations solver categories